Interventions for improving teamwork in intrapartum care: a systematic review of randomised controlled trials. Issue 1 (10th October 2019) - Wu, Michael; Tang, Jennifer; Etherington, Nicole; Walker, Mark; Boet, Sylvain
Abstract : Background: The labour and delivery environment relies heavily on interdisciplinary collaboration from anaesthesiologists, obstetricians and nurses or midwives to deliver optimal patient care. A large number of adverse events in obstetrics are associated with failure in communication and teamwork among team members, with substantive consequences. The objective of this study is to perform a systematic review of interventions aimed at improving teamwork in obstetrics. Methods: This systematic review identified and assessed randomised controlled trials (RCTs) of interventions aimed at improving teamwork among interdisciplinary teams in obstetrical care. Medline, CENTRAL, CINAHL and Embase were searched for studies evaluating one of: patient outcomes, team performance or processes of clinical efficiency. Identified citations were reviewed in duplicate for eligibility. Results: Nine RCTs met the inclusion criteria; five of these RCTs were conducted under simulated clinical environments. Simulation-based teamwork training interventions were the most represented (n=7 studies, 3047 healthcare providers (HCPs), 107 782 births), followed by checklists (n=1 study, 136 HCPs) and an electronic-based decision support tool (n=1 study, 296 HCPs). Simulation-based teamwork training was found to improve team performance in 100% of relevant studies (3 of 3 studies assessing team performance) and patient morbidity in 75% of relevant studies (3 of 4 studies assessing patient morbidity). However, no direct mortality benefit was identified among all the studies reviewed. Studies were assessed to be of low-moderate quality and had significant limitations in their study designs. Conclusion: While the evidence is still limited and from low to moderate quality RCTs, simulation-based teamwork interventions appear to improve team performance and patient morbidity in labour and delivery care. PROSPERO Trial registration number: CRD42018090452